CONSUMER PERCEPTION ANALYSIS OF HERBAVITA: A FUNCTIONAL READY-TO-DRINK SPICE BEVERAGE BASED ON LOCAL WISDOM IN SOUTH LAMPUNG - Tyasto Prima Ahmadi; Aevita Ainun Niha; Lenggo Geni Katlin Jambak; Yulia Puspita Sari (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Ready-to-drink (RTD) herbal drinks are liquid products based on natural ingredients such as spices and medicinal plants that are packaged practically and consumed directly as functional drinks that support health. This study aims to analyze consumer perceptions of Herbavita, a functional ready-to-drink (RTD) herbal drink product based on local wisdom developed in South Lampung. This product is formulated from red ginger and turmeric with varying ratios, then tested using the hedonic method by 20 respondents. The study used a mixed methods approach with quantitative analysis through assessments of taste, aroma, and color, as well as qualitative analysis of criticism and suggestions for product development. The results showed that the sample with a balanced composition (50% red ginger and 50% turmeric) obtained the highest score for all sensory parameters, indicating consumer preference for balanced taste and aroma. Respondent profile analysis revealed that the majority were from the young age group and domiciled in Pasuruan, with a relatively balanced gender distribution. Suggestions from respondents emphasized the importance of attractive, functional, and informative packaging design as a supporting factor for product appeal. These findings demonstrate that product innovations based on traditional ingredients can be well-received if presented in a format that aligns with modern consumer preferences. Therefore, combining traditional values with innovative approaches is key to developing adaptive, competitive, and sustainable RTD spiced beverage products.